Effect of Alumina as an Anti-Soiling Nanomaterial for Enhancing Photovoltaic Performance - Ala H. S. Alardah; Alfajer M. Alrasheed; Fatima Ahmad Alemadi; Sumalatha Bonthula; Enas Fares; Rajender Boddula; Ahmed Bahgat Radwan; Noora Al-Qahtani (Materials Proceedings, 2024)
Anti-soiling coatings are an essential tool for repelling or protecting surfaces from all sorts of particles, sand, and dust. It is usually used on photovoltaic (PV) cells and solar cells to generate electricity in dry regions such as Qatar and the Gulf countries. However, due to soiling, the performance of solar and PV cells significantly degrades, and they are unable to achieve their potential for success. Thus, an anti-soiling coating is applied to prevent dust accumulation, which interferes with the function of solar panels by restricting the required power output. In this study, an alumina nanomaterial was used in the preparation of the ink, which was coated onto a normal glass substrate using the spin coating technique, and the coated samples were characterized using SEM and XRD. The results showed that the coating was able to significantly reduce the surface energy of the glass substrate while improving its hydrophobicity. The anti-soiling performance of the coating was evaluated using a gravimetric method, which showed that the coating had excellent anti-soiling properties. The reference and coated glass substrates were placed outdoors for a given period of time, and the results showed that the amount of dust that was deposited on the coated sample that was outdoors was greatly reduced.